Visi Pendidikan Berdasarkan Konsep Panggilan: Upaya Menemukan Arah yang Menyatukan Pendidikan Kristen di Berbagai Konteks - Sutrisna Harjanto (Asosiasi Teolog Indonesia, 2019)
Fragmentation constitutes a classic phenomenon for Christian education in various contexts, one that is not easily addressed despite the many attempts leaders and thinkers in Christian education have explored. The ongoing fragmentation indicates lack of a comprehensive vision that might unify the direction of Christian education in various contexts. In this article, the author proposes that a vision for Christian education be based on the concept of calling as understood from the framework of a biblical metanarrative, to provide a unifying trajectory for Christian education within various contexts (family, school, church, parachurch, and seminaries) by which such efforts can be seen as complementary and synergistic. The need for collaboration and synergy among various and widely differing educational contexts is illustrated by a certain qualitative study that traces the process of formation as experienced by a number of Christian professionals in ways that enable them to live out their vocational work as the Lord’s call (vocation) as well as to dedicate their lives according to the interest of others. This need for collaboration and synergy also finds confirmation in the theory of human development ecology as proposed by developmental psychology expert, Urie Bronfenbrenner.